USING PADLET IN LANGUAGE LEARNING:AN INNOVATIVE APPROACH TO LEARNING (Web of Teachers: Inderscience Research, 2025)
With the development of digital technologies and the increasing introduction of information and communication technologies in the educational process, traditional methods of teaching foreign languages are undergoing significant changes. Modern educational technologies, such as online learning platforms, provide teachers and students with new opportunities for a more interactive and engaging learning experience. One such tool is Padlet, an online platform for creating virtual whiteboards on which text, images, videos, audio files and other materials can be placed. This makes Padlet a powerful tool for learning, especially when learning foreign languages. The article discusses the application of Padlet in foreign language teaching as a tool for activating the learning process, as well as investigating the pedagogical advantages arising from its use.